O consumo do sentido: práticas de vida de Downton Abbey como discurso publicitário - Prando, Lye Renata (2019)
This research investigates how Downton Abbey brand designers structure their speeches to expose aristocratic lifestyles on the show and later on Downton Abbey at home website. From the series, it seeks to identify the discursive mechanisms used - enunciative, thematic and figurative - to make the enunciator accept the proposed simulacrum and how these statements are employed by advertisement discourse to sell products that are circulating in the series scenes on the website. Identifying the generative path of meaning, systematizing themes and figures, values axiology, and analyzing the interaction and meaning regimes, we enable the approval between content scheme and expression scheme. The choice of a vintage series about the aristocracy is motivated by these enquirers action, who present lifestyle with a perspective of the past, but with current issues, and by the growing movement of trans mediatic strategies provided by technology progress. The cataloging led to a corpus consisted of the ways of eating presented in the series six seasons and of the products commercialized by Downton Abbey at home website that are a part of these scenes. The theoretical and methodological foundation is Greimas' semiotics, beyond its complementation in Landowski' socio semiotics, with deepening in circulating values role, in the interactions regimes of meaning apprehension and construction; from Floch and Oliveira elaborations on figurativeness, identifying themes, figures and homologations between content scheme and expression scheme; from semiotic contributions in advertising, such as Martyniuk. The basis for transmedia discussions follows Fechine and Jenkins' studies, and Baudrillard simulacrum studies. The research pointed out that Downton Abbey brand discourses, in various medias, show a positive construct of aristocracy simulacrum, giving visibility to values such as wealth, well-being, tranquility, sophistication and time, approaching to the imaginary of individuals who appropriate of this discourse. Downton Abbey enunciates, through the ways of eating, a lifestyle to reiterate these values, materialized by products for sale available on Downton Abbey at home website. This study promoted an approximation between semiotics and advertising, offering a scientific framework for consumption strategies